The first 1001 days: A scoping review of parenting interventions strengthening good enough parenting in parents with intellectual disabilities - Zijlstra, Annick; Joosten, Daniek; van Nieuwenhuijzen, Maroesjka; de Castro, Bram Orobio (Journal of intellectual disabilities, 2025)
There are concerns about parents' parenting skills with intellectual disabilities. However, it is reported that parents with intellectual disabilities show good enough parenting if they are supported effectively and in line with their needs. This scoping review identifies and critically evaluates preventive interventions for parents with intellectual disabilities a cumulation of multiple and complex problems that aim to prepare them for good enough parenting. Six interventions were identified, with preliminary to strong indications of effectiveness. Although none of the interventions focused on all conditions of good enough parenting and only one intervention incorporated all seven key elements to effectively work with parents with intellectual disabilities, the limited evidence on the effectiveness of these interventions suggests that significant and societally relevant effects on parents' knowledge and skills can be attained. This suggests that more comprehensive early preventive interventions with rigorous evaluations can have a significant impact.